PPARγ agonists negatively regulate αIIbβ3 integrin outside‐in signaling and platelet function through up‐regulation of protein kinase A activity. (7th February 2017) - Unsworth, A. J.; Kriek, N.; Bye, A. P.; Naran, K.; Sage, T.; Flora, G. D.; Gibbins, J. M.
Abstract : Essentials peroxisome proliferator‐activated receptor γ (PPARγ) agonists inhibit platelet function. PPARγ agonists negatively regulate outside‐in signaling via integrin αIIbβ3. PPARγ agonists disrupt the interaction of Gα13 with integrin β3. This is attributed to an upregulation of protein kinase A activity. Summary: Background: Agonists for the peroxisome proliferator‐activated receptor (PPARγ) have been shown to have inhibitory effects on platelet activity following stimulation by GPVI and GPCR agonists. Objectives: Profound effects on thrombus formation led us to suspect a role for PPARγ agonists in the regulation of integrin αIIbβ3 mediated signaling. Both GPVI and GPCR signaling pathways lead to αIIbβ3 activation, and signaling through αIIbβ3 plays a critical role in platelet function and normal hemostasis. Methods: The effects of PPARγ agonists on the regulation of αIIbβ3 outside‐in signaling was determined by monitoring the ability of platelets to adhere and spread on fibrinogen and undergo clot retraction. Effects on signaling components downstream of αIIbβ3 activation were also determined following adhesion to fibrinogen by Western blotting. Results: Treatment of platelets with PPARγ agonists inhibited platelet adhesion and spreading on fibrinogen and diminished clot retraction. A reduction in phosphorylation of several components of αIIbβ3 signaling, including the integrin β3 subunit, Syk, PLCγ2, focal adhesion kinase (FAK) and Akt, was also observed as a result of reduced interaction of the integrin β3 subunit with Gα13. Studies of VASP phosphorylation revealed that this was because of an increase in PKA activity following treatment with PPARγ receptor agonists. Conclusions: This study provides further evidence for antiplatelet actions of PPARγ agonists, identifies a negative regulatory role for PPARγ agonists in the control of integrin αIIbβ3 outside‐in signaling, and provides a molecular basis by which the PPARγ agonists negatively regulate platelet activation and thrombus formation.